Human Capital Implementation Strategy in the Kamala Fertility Clinic - Yudi Eriyanto; Ratna Indrawati Lestariani; Tantri Yanuar Rahmat Syah; Rhian Indradewa (Penerbit Kemala Indonesia, 2021)
Currently, the increasingly fierce competition in the health business encourages companies to develop innovative strategies in meeting human resource needs. To capture market needs, companies must have added value to their resources, especially for the expert resources. Kamala Clinic is the main clinic providing fertility and gynaecology special health services. Under PT. Medika Sehat Utama, Kamala clinic located in the golden triangle of Bekasi city-West Java, is committed to developing fertility and gynaecology clinics by offering a guaranteed IVF program (self-insurance). Providing maximum service supported by experienced experts. To meet the dynamic needs of patients, a strong HR recruitment strategy who is always able to keep up with the times is needed. Thus, this study aims to analyse the human capital strategies at the Kamala Clinic that offers IVF programs with self-insurance. In the implements fertility specialist selection strategies to enhance the clinic's reputation. This is inseparable from the selection and recruitment to meet competency needs. Thus, these results are expected to be a reference for other IVF clinics in developing more optimal services.